Expression of Senescence and Apoptosis Biomarkers in Synchronous Bilateral Breast Cancer: A Case Report. - Saleh, Tareq; El-Sadoni, Mohammed; Alhesa, Ahmad; Awad, Heyam; Jaradat, Mahmoud; Al-Hazaimeh, Mohammad; Dawoud, Rand; Mryyian, Amel; Azab, Bilal (Current Oncology, 2021)
Background: Synchronous bilateral breast cancer (SBBC) provides a special condition where two independent breast tumors are exposed to cancer pharmacotherapy within a uniform pharmacokinetic milieu. Both senescence and apoptosis are established responses to therapy; however, they have potentially variable contributions to the overall outcome of treatment, which are yet to be determined. Methods: In this report, we describe the clinicopathological picture of two SBBC cases that received standard anticancer treatment and assess their expression profile of several molecular hallmarks of senescence and apoptosis. Results: Our analysis identified that synchronous tumors have variable expression profiles of both senescence- and apoptosis-associated biomarkers, despite comparable pathological responses to neoadjuvant chemotherapy and current survival rates. Conclusions: Our results highlight the variable expression of senescence- and apoptosis-associated markers in breast tumors (despite the shared somatic genetic background) and invites a large-scale assessment of both senescence and apoptosis in breast cancer tissue in vivo and their contribution to the pathological response and overall survival.